HISTORIC CITIES IN EMERGING COUNTRIES. ECONOMICS OF CONSERVATION REVISITED - Ost, Christian (BDC. Bollettino Del Centro Calza Bini, 2013)
In 2012, UNESCO celebrated the 40th anniversary of the adoption of the Convention for the Conservation of the Architectural Heritage. The protection and preservation of the world built heritage has been since so successful that we face today a new challenge in managing the heritage in a context of threatening macroeconomic factors: mass-tourism, urban development, restructuring, market dominance, climate changes, etc. The paper aims to revisit economics of conservation in the framework of historic cities in emerging countries. That entails the need for the sound assessment of economic values, the development of new monitoring tools, and decision-making process. It also put emphasis on new partnerships between public and private initiatives in historic cities.